The concept of divine science for Abu Al-Hassan Al-Ameri - Annad, Ali Jabbar (Al-Adab Journal, 2015)
This research deals with one of the figures in the history of Islamic Philosophy, Abu al-Hassan Mohamed Bin Yousef Al Amiri Khayyam Al-Nishapuri " died (381AH)he has several publications in Islamic philosophy, sociology talk, the most prominent of which are: His Excellency د, chapters in the divine providence and guidance to correct belief. It is where the subject abut God , God knowledge of the cause of happiness, His Excellency human knowledge after God and communication him. .. This research is divided into several axs, qualities of Allah, Allah reunited and existence, related to the presence of Allah, Allah, a source of happiness. The qualities of Allah, Al Amiri is Allah, who is real, and everything else in the presence of a minus non-genuine, and Allah is the updates things , photos, these views are derived from Islamic environment, whether philosophical or religious with nothing to reconcile Greek philosophy and religion, and there is a clear impact of Canadian philosophy Al farabi the philosophy of Al Amiri..It has evidence of the presence of Allah guide and feasible due evidence cosmic God, is the reason for the access of happiness, through his knowledge, and this talk we find when philosophers who believe in Islam theory Faid, communication with God is the source of joy and happiness. This is like the opinion of Ibn Khaldoun Center and Abu Hayyan